1997
DOI: 10.1038/sj.bjp.0701312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of sibutramine and other monoamine reuptake inhibitors on food intake in the rat

Abstract: 1 The e ects of the potent 5-hydroxytryptamine (5-HT) and noradrenaline reuptake inhibitor (serotonin-noradrenaline reuptake inhibitor, SNRI), sibutramine, on the cumulative food intake of freely-feeding male Sprague-Dawley rats during an 8 h dark period were investigated and compared to those of the selective 5-HT reuptake inhibitor (selective serotonin reuptake inhibitor, SSRI),¯uoxetine; the selective noradrenaline reuptake inhibitor, nisoxetine; the 5-HT and noradrenaline reuptake inhibitors, venlafaxine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 32 publications
7
79
1
1
Order By: Relevance
“…Corwin et al found that the dopamine agonist, Damphetamine and fenfluramine, a serotonin agonist, did not reliably alter the 22-h stimulus in chronically food-restricted animals trained to discriminate between food presented 22 or 3 h before the experimental session. Previous research assessing the effects of sibutramine and other monoamine reuptake inhibitors on food intake indicated enhancing both serotonin and norepinephrine resulted in a significant reduction in food intake, whereas selective increases of either serotonin or norepinephrine were not effective (Jackson et al 1997b). …”
Section: Discussionmentioning
confidence: 99%
“…Corwin et al found that the dopamine agonist, Damphetamine and fenfluramine, a serotonin agonist, did not reliably alter the 22-h stimulus in chronically food-restricted animals trained to discriminate between food presented 22 or 3 h before the experimental session. Previous research assessing the effects of sibutramine and other monoamine reuptake inhibitors on food intake indicated enhancing both serotonin and norepinephrine resulted in a significant reduction in food intake, whereas selective increases of either serotonin or norepinephrine were not effective (Jackson et al 1997b). …”
Section: Discussionmentioning
confidence: 99%
“…In addition,¯uox-etine and nisoxetine, which are selective reuptake inhibitors of 5-HT and noradrenaline respectively, have no eect on food intake when given alone, but they profoundly inhibit food intake when given in combination (equivalent to sibutramine's action), demonstrating a synergistic interaction of those two monoamines in the control of ingestive behaviour (Jackson et al, 1997a). The use of selective monoamine antagonists has con®rmed that the acute satiety-inducing eects of sibutramine involves a 1 and b 1 adrenoceptors, as well as 5HT c and possibly 5HT 2A receptors (Jackson et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…by gavage for a period of 21 days. This dose has previously been shown to be eective at reducing food intake in the rat and reduces food intake by 50% over a 2 h period (Jackson et al, 1997a). Lean and dietary-obese controls similarly received an equal volume of deionized water.…”
mentioning
confidence: 99%
“…Several brain area co-express serotonin and cannabinoid receptors [126]. Sibutramine, a serotonin-and noradrenalin-reuptake inhibitor, inhibits appetite, promotes weight loss and increases thermogenesis in brown adipose tissue [127,128]. Besides, the administration of this drug is also associated to undesirable side-effects [129].…”
Section: Efficacy Of Combined Therapy For Obesitymentioning
confidence: 99%